The challenges of local development for network territories in the southeast of the State of Pará – Brazil - Alves do Nascimento, Aristóteles; do Socorro Almeida Flores, Maria; Quaresma Maneschy, Rosana; Fernando Paes de Queiroz, Luiz (Seven Editora, 2023)
The incidence of network territories, in the territorial limits of the Amazon of Pará, conceived and categorized to guarantee the strategic development of transition to sustainability, culminated in the formation of new dynamics and territorialities. Thus, the objective of this work was to analyze the challenges of local development in network territories in southeastern Pará. Therefore, due to the qualitative multidisciplinary approach, the analytical-descriptive-critical scientific method was used, followed by evaluations, anchors to territorial approaches, and reflections, on the challenges of local development, especially in the areas present in the productive systems of Araguaia-Tocantins. As a result, it is observed that the notion of the conception of this territorial unit, brought by the Macrozoning of the Legal Amazon, must be relativized because it is possible to perceive that in the process of development of territorialization policies to convergence, there has been a resurgence of inter-regional asymmetries. regional, implying challenges with a focus on local and regional development, thus reinforcing the role of the State in articulating and providing local leadership, through socio-territorial organization and innovation in development processes.DOI: https://doi.org/10.56238/devopinterscie-114